2015
DOI: 10.1515/hmbci-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Retinol binding protein 4 and its membrane receptors: a metabolic perspective

Abstract: Nearly a decade of intense research has passed since the first report linking circulating retinol binding protein 4 (RBP4) to the development of insulin resistance. By now, a variety of underlying mechanisms have been identified; some of them are adherent to the canonical role of this circulating protein, which is to transport and deliver retinol to target tissues, and others that seem rather independent of retinol transport. Despite all these efforts, a consensus in the basic principles of RBP4's metabolic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 104 publications
0
20
0
Order By: Relevance
“…RBP4 and its associated RA have been shown to trigger several downstream pathways to confer insulin resistance [ 16 19 ]. The pathways could also be shared in promoting cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RBP4 and its associated RA have been shown to trigger several downstream pathways to confer insulin resistance [ 16 19 ]. The pathways could also be shared in promoting cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidences showed that overexpression of RBP4 from adipose tissues promote hyperinsulinemia and type II diabetes [ 11 15 ]. Several pathways have been identified mediate RBP4 signaling [ 16 ]. RA and its oxidative products can activate retinoic acid receptors and retinoid X receptors and promote glucose production in liver [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we characterized a novel RBP4 gain-of-function mouse model and show that an elevation of liver-secreted RBP4 to serum levels as observed in the obese, insulin-resistant state does not impair glucose homeostasis in mice. Thus, although increased levels of circulating RBP4 associate with glucose intolerance and insulin resistance (12), they are unlikely to be a causative factor. However, RBP4 may exhibit local functions in organs such as adipose tissue whose investigation could help to reconcile the divergence of previous reports.…”
Section: Liver Rbp4 and Glucose Homeostasismentioning
confidence: 99%
“…These findings supported the notion of RBP4 working as adipokine, and it was hypothesized that an increased expression in adipose tissue of obese subjects leads to higher serum levels that, in turn, induce insulin resistance. So far, a variety of mechanisms of how RBP4 causes glucose intolerance and insulin resistance were reported (12), most prominently a RBP4-driven inflammatory response in adipose tissue involving the activation of antigen presentation and T cells (6,13,14).…”
mentioning
confidence: 99%
“…This is an intriguing observation because of the recent identification of retinol-binding protein (RBP4) as an adipokine, as well as RBP4’s association with breast cancer (6062). RBP4 secreted from the liver is the sole transport protein for retinol in the blood, with circulating levels of retinol tightly correlating with circulating RBP4 levels (63, 64).…”
Section: Discussionmentioning
confidence: 99%